Hubungan Sense of School Belonging dan Subjective Well-Being Siswa Madrasah Tsanawiyah di Pondok Pesantren - Firdaus, Hilma Aprillia; Darmawanti, Ira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the relationship between sense of school belonging and subjective well being in MTs students who live in boarding schools. This research uses quantitative methods. The subjects in this study were MTs students who lived in boarding school X with a sample size of 118 students. The data collection technique was a questionnaire. The research instruments used were the PSSM scale which had been modified in the boarding school setting and the subjective well-being scale. Hypothesis testing used in data analysis techniques is product moment correlation which produces a correlation coefficient value of 0.303. The results of this study indicate that there is a significant and unidirectional relationship between sense of school belonging and subjective well-being in MTs students who live in boarding schools. Other findings in this study indicate that the level of sense of school belonging and subjective well-being in MTs students in boarding school X is included in the moderate category.